Democratic justice - Shapiro, Ian. (New Haven, CT : Yale University Press, 1999)
"Democracy and justice are often mutually antagonistic ideas, but in this innovative book Ian Shapiro shows how and why they should be pursued together. Justice must be sought democratically if it is to garner legitimacy in the modern world, he claims, and democracy must be justice-promoting if it is to sustain allegiance over time. Democratic Justice meets these criteria, offering an attractive vision of a practical path to a better future."--BOOK JACKET.
1. Why Democratic Justice? -- 2. Preliminaries -- 3. The General Argument -- 4. Governing Children -- 5. Consenting Adults -- 6. Controlling Work -- 7. Life's Ending -- 8. Deepening Democratic Justice.
Includes bibliographical references.
Keywords: Family law; Justice; Democracy; Political planning; Family policy; Labor policy; Older people -- Government policy